Characterization of fsr, a Regulator Controlling Expression of Gelatinase and Serine Protease in Enterococcus faecalis OG1RF - Qin, Xiang (American Society for Microbiology, 2001)
We have previously identified a locus, fsr, a homologue of staphylococcal agr loci, which positively regulates the expression of gelatinase and serine protease (encoded by gelE and sprE, respectively) in Enterococcus faecalis OG1RF. The expression of the three genes in the fsr locus, fsrA, fsrB, and fsrC, appears to be autoregulated, and we have shown that mutants with insertion disruptions in each of these three genes were significantly attenuated in a mouse peritonitis model compared to the parent strain. In the present study, we showed that fsrB and fsrC are highly expressed in the postexponential growth phase and that their expression is cell density dependent. Reverse transcriptase PCR using primers covering the intergenic regions in the fsr/gelE loci confirmed that fsrB and fsrC, as well as gelE and sprE, are cotranscribed. We also showed, using a nonpolar fsrB deletion mutant, that fsrB, the homologue of agrB of staphylococci with unknown function, is required for the regulatory function of fsr. Primer extension and analysis of transcriptional fusions indicated the presence of promoters immediately upstream of fsrA, of fsrB, and of gelE and that the fsrB and gelE promoters are fsr dependent, while the fsrA promoter is an fsr-independent weak constitutive promoter. Two conserved 7-bp direct repeats were found immediately upstream of the fsrB and gelE promoters, similar to the repeats found upstream of P2 and P3 promoters of the agr locus; deletions and mutations in the repeated sequences completely abolished the fsrB and gelE promoter activities, suggesting that the repeats are important for the regulatory function in the fsrB and gelE promoter regions.